Mass spectrometry and ion mobility study of poly(ethylene glycol)‐based polyurethane oligomers. (8th February 2020) - Harris, Rachel A.; Picache, Jaqueline A.; Tomlinson, Ian D.; Zlibut, Emanuel; Ellis, Berkley M.; May, Jody C.; McLean, John A.; Hercules, David M.
Abstract : Rationale: Commercial‐grade polymer synthesis is performed via melt polymerization, which leads to polydispersion. The work reported herein provides a synthetic strategy to produce mono‐dispersive polyurethane oligomers and an analytical strategy to distinguish these oligomers, providing chemists with the tools necessary to synthesize and identify specific polymer structures that exhibit a desired property. Methods: Three isomeric poly(ethylene glycol)–polyurethane (PEG‐PUR) oligomers were synthesized and analyzed via flow‐injection ion mobility mass spectrometry (IM‐MS). Each polymer oligomer was injected and run independently via flow injection at 100 μLmin −1 and analyzed in positive ion mode on a drift tube quadrupole time‐of‐flight (QTOF) instrument. Mobility measurements were determined using a single‐field approach. For tandem mass spectrometry (MS/MS) experiments, the sodium‐adducted singly charged precursor ion was isolated in the quadrupole and subjected to a range of collision energies. Results: In MS experiments, both +1 and +2 sodium‐adducted species were observed for each oligomer at m/z 837.4 and 430.2, respectively. When isolated and fragmented via MS/MS, the +1 precursor yielded distinct product ions for each of the three isomeric oligomers. Fragmentation generally occurred at urethane linkages via 1, 3‐ and 1, 5‐H shift mechanisms. IM was also used to distinguish the three isomers, with greater IM separation observed for the +2 versus the +1 species. Conclusions: Mono‐disperse PEG‐PUR oligomers were synthesized and analyzed. Although the polymeric oligomers analyzed in this study are quite small and structurally simple, this work serves as a model system for the synthesis and structural characterization of larger, more complex block copolymers.